2008
DOI: 10.1007/s10623-008-9223-5
|View full text |Cite
|
Sign up to set email alerts
|

Tight sets, weighted m-covers, weighted m-ovoids, and minihypers

Abstract: Minihypers are substructures of projective spaces introduced to study linear codes meeting the Griesmer bound. Recently, many results in finite geometry were obtained by applying characterization results on minihypers [8,17,18]. In this paper, using characterization results on certain minihypers, we present new results on tight sets in classical finite polar spaces and weighted m-covers, and on weighted m-ovoids of classical finite generalized quadrangles. The link with minihypers gives us characterization res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In this section we present the characterization of i-tight sets in the Hermitian variety H(2r + 1, q) and in the symplectic polar space W (2r + 1, q) when i < (q 2/3 − 1)/2. This result is the improvement of the result from [13] where the upper bound on i was q 5/8 / √ 2 + 1. Combining the generalized version of known techniques [26] with recent results on blocking sets and minihypers, we present an alternative proof of this result and consequently improve the upper bound on i to (q 2/3 − 1)/2.…”
Section: Tight Sets In Finite Classical Polar Spacesmentioning
confidence: 48%
“…In this section we present the characterization of i-tight sets in the Hermitian variety H(2r + 1, q) and in the symplectic polar space W (2r + 1, q) when i < (q 2/3 − 1)/2. This result is the improvement of the result from [13] where the upper bound on i was q 5/8 / √ 2 + 1. Combining the generalized version of known techniques [26] with recent results on blocking sets and minihypers, we present an alternative proof of this result and consequently improve the upper bound on i to (q 2/3 − 1)/2.…”
Section: Tight Sets In Finite Classical Polar Spacesmentioning
confidence: 48%
“…Result 1 has more applications. We mention the following one, which improves [4,Corollary 5.10]. For this we consider a map w of the line set of Q (4, q) to the set of non-negative integers.…”
Section: Another Application Of the Results On Blocking Sets In Quadricsmentioning
confidence: 99%
“…In [19], it has been shown that an i-tight set T of W (2r +1, q), Q + (2r +1, q), or H(2r+1, q) is a set of iθ r points intersecting every hyperplane in at least iθ r−1 points, hence T is an (iθ r , iθ r−1 ; 2r + 1, q)-minihyper. Using characterization results about minihypers of [19] and [29], it is possible to characterize i-tight sets in the aforementioned polar spaces.…”
Section: Minihypers and I-tight Setsmentioning
confidence: 99%
“…Using characterization results about minihypers of [19] and [29], it is possible to characterize i-tight sets in the aforementioned polar spaces.…”
Section: Minihypers and I-tight Setsmentioning
confidence: 99%